An editor for the generation and customization of geometry restraints. Issue 2 (1st February 2017) - Moriarty, Nigel W.; Draizen, Eli J.; Adams, Paul D.
Abstract : Obtaining a restraint dictionary for novel ligands or improving restraints for known ligands can require their manual modification. This can be tedious and error‐prone. REEL is a restraints editor that provides quick, easy and accurate development, allowing global changes and fine‐tuning of individual restraints. Abstract : Chemical restraints for use in macromolecular structure refinement are produced by a variety of methods, including a number of programs that use chemical information to generate the required bond, angle, dihedral, chiral and planar restraints. These programs help to automate the process and therefore minimize the errors that could otherwise occur if it were performed manually. Furthermore, restraint‐dictionary generation programs can incorporate chemical and other prior knowledge to provide reasonable choices of types and values. However, the use of restraints to define the geometry of a molecule is an approximation introduced with efficiency in mind. The representation of a bond as a parabolic function is a convenience and does not reflect the true variability in even the simplest of molecules. Another complicating factor is the interplay of the molecule with other parts of the macromolecular model. Finally, difficult situations arise from molecules with rare or unusual moieties that may not have their conformational space fully explored. These factors give rise to the need for an interactive editor for WYSIWYG interactions with the restraints and molecule. Restraints Editor, Especially Ligands ( REEL ) is a graphical user interface for simple and error‐free editing along with additional features to provide greater control of the restraint dictionaries in macromolecular refinement.